2010
DOI: 10.1021/jz100963y
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Discrete Au Nanoparticle Collisions by Electrocatalytic Amplification Using Pt Ultramicroelectrode Surface Modification

Abstract: After growing a thin layer of oxide (PtO x ) by anodization of a Pt electrode, it changed from catalytically active for electrochemical NaBH4 oxidation into an inactive electrode. When held at a potential where the oxide film was maintained, collisions of individual 14 nm diameter Au nanoparticles (NPs) that catalyzed NaBH4 oxidation were successfully observed as discrete current pulses (spikes or blips) for each NP interaction with the modified Pt electrode via amplification from NaBH4 oxidation. The current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
120
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(130 citation statements)
references
References 16 publications
6
120
0
4
Order By: Relevance
“…This has since been applied to a range of catalysed reactions including oxygen reduction, [20] water oxidation [21] and sodium borohydride oxidation. [22] The characterisation of NPs by their direct electrolysis has also been applied to a range of NP materials including metal, [23][24][25] metal oxide, [26] organic [27] and polymeric NPs. [28] When a NP collides with the electrode, a transient spike in current is observed and the charge passed can be directly related to its size.…”
Section: Introductionmentioning
confidence: 99%
“…This has since been applied to a range of catalysed reactions including oxygen reduction, [20] water oxidation [21] and sodium borohydride oxidation. [22] The characterisation of NPs by their direct electrolysis has also been applied to a range of NP materials including metal, [23][24][25] metal oxide, [26] organic [27] and polymeric NPs. [28] When a NP collides with the electrode, a transient spike in current is observed and the charge passed can be directly related to its size.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Chronoamperometric measurements of inorganic NPs have been mostly carried out at solid electrodes. [19][20][21][22][23][24][25][26] Recently, a very extensive work on the collision of NPs at microelectrodes (Pt, Au and glassy carbon) was presented by the groups of Bard and Compton. They made a clear distinction between electrocatalytic processes occurring at the surfaces of the NPs [23][24][25][26] and oxidation events of single NPs colliding with the electrode.…”
Section: Introductionmentioning
confidence: 99%
“…They made a clear distinction between electrocatalytic processes occurring at the surfaces of the NPs [23][24][25][26] and oxidation events of single NPs colliding with the electrode. [22,23] Bard et al, observed the collision of single Pt NPs with a carbon electrode by electrocatalytic amplification of H þ ion reduction, where the redox process was identified to occur on the surface of the Pt NPs. [22] In order to measure the size and concentration of the NPs, current research is using the faradaic current transient signals obtained by direct electrooxidation of NPs themselves (preferably Ag and Au NPs) as well as the bulk deposition (electroplating) and underpotential deposition of a metal onto NPs during collisions with an inert electrode surface.…”
Section: Introductionmentioning
confidence: 99%
“…We broadly define NIE as any method based on the electrochemical detection of discrete NPs in solution as they collide with the surface of an electrode. [1][2][3][4][5][6][7] The ability to probe individual microscopic particles in solution with UMEs has inspired fundamental studies of single NP electrochemistry and NP/electrode interactions, [8][9][10][11][12][13][14][15][16][17] diffusive and electro/magnetophoretic particle transport, [18][19][20][21][22] and the development of electrochemical bioassays with single-molecule sensitivity. [23][24] Colloidal stability [25][26] is of critical importance for the accurate interpretation of NP/electrode impacts.…”
mentioning
confidence: 99%